2014
DOI: 10.1002/joc.4208
|View full text |Cite
|
Sign up to set email alerts
|

An 850‐year tree‐ring‐based reconstruction of drought history in the western Qilian Mountains of northwestern China

Abstract: Studies of regional drought history will be helpful for understanding current hydroclimate variability with global warming as well as predicting future hydroclimate shifts. Long‐term tree‐ring records are scarce in the western Qilian Mountains of northwestern China, which is also the western boundary of the natural distribution of Qilian Juniper (Juniperus przewalskii Kom.) in this area. Here, we present an 850‐year (AD 1161–2010) reconstruction of May–July self‐calibrating Palmer Drought Severity Index (scPDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 55 publications
(75 reference statements)
3
39
0
Order By: Relevance
“…In addition, high temperature in May leads considerable evaporation from the soil and transpiration from leaves, causing drought stress on cambial activity. However, the influence of drought is not as strong as that reported in other studies at lower elevations (Gou et al, 2014;Liu Lusan et al, 2006;Shao et al, 2005;Zhang et al, 2003), suggesting that more soil moisture is available at high elevations due to lower evaporation and higher precipitation. Thus, the moisture-triggered onset of cell division could only play a weaker role than low temperature in controlling the whole ring width of Qilian juniper at the upper treeline.…”
Section: Growth Response Of Qilian Juniper To Climatic Factors In Thementioning
confidence: 72%
“…In addition, high temperature in May leads considerable evaporation from the soil and transpiration from leaves, causing drought stress on cambial activity. However, the influence of drought is not as strong as that reported in other studies at lower elevations (Gou et al, 2014;Liu Lusan et al, 2006;Shao et al, 2005;Zhang et al, 2003), suggesting that more soil moisture is available at high elevations due to lower evaporation and higher precipitation. Thus, the moisture-triggered onset of cell division could only play a weaker role than low temperature in controlling the whole ring width of Qilian juniper at the upper treeline.…”
Section: Growth Response Of Qilian Juniper To Climatic Factors In Thementioning
confidence: 72%
“…8; Zhang et al, 2013;Chen et al, 2015;, and were significantly increasing in the western and middle Qilian Mountains (T11 and T12; Fig. 8; Gou et al, 2015b). In contrast, moisture conditions in the LLM presented an opposite trend (LLM; Fig.…”
Section: Drought Dynamics In Arid Region Of the Northwest Chinamentioning
confidence: 92%
“…A PDSI dataset on a 2.5°×2.5° grid that was developed by Dai et al (2004) had been widely used as the variable of climate reconstructions (Cook et al, 2004;Nicault et al, 2008;Peng and Liu, 2013;Gou et al, 2015b). The newly revised sc_PDSI index improves its ability to measure changes in aridity and to examine the effects of individual forcing on the aridity trend (Dai, 2012).…”
Section: Climate Datamentioning
confidence: 99%
“…Inner and northern Asia is also one of the most sensitive areas to climate change in Asia, and many treering-based climate reconstructions have been conducted in this area (Briffa et al 1995;Esper et al 2001Esper et al , 2010Pederson et al 2001;Solomina et al 2007;Agafonov and Kukarskikh 2008;Magda et al 2011;Chen et al 2013Chen et al , 2015Liu et al 2013;Gou et al 2014;Bao et al 2015). Dendroclimatological studies at the high-latitude sites of northern Asia have been focused on temperature reconstruction and provided the information about the summer temperature variations and recent global warming (Briffa et al 1995(Briffa et al , 2013Naurzbaev et al 2002;Esper et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies revealed that the role of temperature as a limit factor of tree growth was shown to decrease from high latitude to low latitude (Fritts 1976;Hantemirov et al 2000;Agafonov and Kukarskikh 2008;Kucherov 2010;Briffa et al 2013). On the contrary, the effect of drought and precipitation on tree growth was increased gradually from northern Asia to inner Asia (Pederson et al 2001;Magda et al 2011;Chen et al 2013Chen et al , 2015Liu et al 2013;Gou et al 2014;Bao et al 2015). In recent years, some dendroclimatic reconstruction precipitation and drought index have also been developed from lower elevation sites at the junction area of inner and northern Asia where the forest vegetation is in contact with the steppe vegetation (Davi et al 2009;Kucherov 2010;Chen et al 2014;Zhang et al 2014).…”
Section: Introductionmentioning
confidence: 99%